The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1002/1097-0142(19930801)72:3<938::aid-cncr2820720345>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Wilms tumor: Report from the national Wilms tumor study

Abstract: Background. Previous epidemiologic studies have indicated that several factors may be associated with an increased risk of Wilms tumor including paternal occupational exposures, maternal exposure during pregnancy to cigarettes, coffee or tea, oral contraceptives, hormonal pregnancy tests, hair‐coloring products, maternal hypertension, vaginal infection during pregnancy, and higher birth weight of the child. The current study examines the nonoccupational risk factors using questionnaire data from a large nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 11 publications
3
55
1
Order By: Relevance
“…7,[17][18][19] Previous investigations on the association between smoking and a subsequent risk of childhood cancers have generated positive and negative results. 22,23,[33][34][35][36] The negative finding from our study, as well as an earlier study 37 on GCT, might be a result of the finding that the carcinogenic effect of smoking is offset by its antiestrogenic effect. 18,19 Whereas alcohol and its metabolites have been shown to be teratogenic, mutagenic, and carcinogenic, 38 -40 the relation between alcohol consumption and childhood cancers has not always been consistent across studies.…”
Section: Discussionsupporting
confidence: 49%
“…7,[17][18][19] Previous investigations on the association between smoking and a subsequent risk of childhood cancers have generated positive and negative results. 22,23,[33][34][35][36] The negative finding from our study, as well as an earlier study 37 on GCT, might be a result of the finding that the carcinogenic effect of smoking is offset by its antiestrogenic effect. 18,19 Whereas alcohol and its metabolites have been shown to be teratogenic, mutagenic, and carcinogenic, 38 -40 the relation between alcohol consumption and childhood cancers has not always been consistent across studies.…”
Section: Discussionsupporting
confidence: 49%
“…Previous case-control studies have shown both increased risk for high birth weight [13][14][15] and no association. [10][11][12] A cohort study in Norway found no association between WT and birth weight. 17 Two other studies have compared case series to standard population data.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found an increased risk of WT based on paternal occupational exposure to various chemicals including pesticides, 4,5 lead or hydrocarbons [6][7][8] and boron. 9 Other exogenous risk factors, such as maternal antibiotic use, 10 household pest extermination, 10 maternal use of hair coloring products, 11 tea consumption, 11 vaginal infections 11 and penthrane exposure, 12 have been associated with WT only in single studies. Birth characteristics as risk factors for WT have been examined with some frequency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Zahm and Ward [15] in their 1998 review found two studies based on the subjects' reports of household or occupational and parental agricultural use of pesticides, which showed elevated risks of Wilms' tumor [39,40]. These findings were not confirmed by other 3 studies of pesticide exposure determined by paternal occupational title or imputed from occupational titles using job-exposure matrices [41][42][43].…”
Section: Wilms' Tumormentioning
confidence: 97%